Synthesis, Physical Properties and Electrochemical Applications of Two Ionic Liquids Containing the Asymmetric (Fluoromethylsulfonyl)(Trifluoromethylsulfonyl)imide Anion - Oriele Palumbo; Giovanni Battista Appetecchi; Giovanna Maresca; Jean-Blaise Brubach; Pascale Roy; Simone Di Muzio; Francesco Trequattrini; Delphine Bordignon; Florine Legrand; Anaïs Falgayrat; Rongying Lin; Sebastien Fantini; et al. (Applied Sciences, 2022)
Novel ionic liquid (IL) electrolytes based on the asymmetric (fluoromethylsulfonyl)(trifluoromethylsulfonyl)imide (FTFSI)− anion, combined with the N-trimethyl-N-butyl-ammonium (N1114)+ and N,N-diethyl-N-methyl-N(2-methoxyethyl)-ammonium (N122(2O1))+ cations, were successfully synthesized and investigated in terms of thermal, vibrational and electrochemical properties. Thermogravimetric measurements revealed that the ionic liquids are stable up to 300 °C (2% mass loss). Differential scanning calorimetry measurements evidenced no phase transition down to −90 °C, suggesting a transition towards a glass state at lower temperatures. Infrared spectroscopy measurements, for the first time performed on ILs containing FTFSI, could not detect any crystallization down to −140 °C. The frequency of the main absorption bands of the ILs are in good agreement with DFT calculations. The FTFSI ionic liquid electrolytes, containing 20% mol of LiTFSI, show no solid-liquid phase transition due to the asymmetry of the FTFSI− anion, increasing the −10 °C conductivity up to 10−4 S cm−1. These interesting ion transport properties remarkably extend the operative temperature range down to low temperatures. The FTFSI electrolytes exhibit remarkable electrochemical stability up to 4.8 V, this making them appealing for realizing safer and highly reliable lithium battery systems operating at high voltages.